PENDAMPINGAN PEMANFAATAN LIMBAH SAYURAN RUMAH TANGGA MENJADI PUPUK ORGANIK CAIR - Hadi Susilo, Joko; Handayani, Tri Astuti; Astuti, Hartiningsih; Agustina Rahmawati, Laily; Endang; Suprastiyo, Ahmad; Erwanto; Surya Atmaja, Dimas; Beny Prasetya, Ammad (Jurnal Abdi Masyarakat, 2024)
Training on the utilization of household vegetable waste into liquid organic fertilizer in Bangle, Sukorame District, Lamongan Regency, aims to increase the awareness and skills of the younger generation in processing organic waste into useful products for agriculture. This program involves the collection of vegetable waste, a fermentation process with the help of EM4 (Effective Microorganisms 4), and the production of quality liquid fertilizer. Prior to the training, participants faced challenges in the form of a lack of knowledge about waste management and dependence on chemical fertilizers. After the training, participants demonstrated significant improvements in understanding and practical skills, with successful application of techniques that reduce waste, improve soil fertility and support plant growth. The success of the training is measured by the application of the techniques taught, positive changes in waste management habits, and tangible results in agriculture. Suggestions for improving program effectiveness include improving initial education, providing adequate facilities and equipment, ongoing support, and using technology. This training makes an important contribution to sustainable agricultural practices and environmentally friendly waste management.